Copine C plays a role in adhesion and streaming in Dictyostelium - Rodney A. Nichols; Amber D. Ide; Cody T. Morrison; Amber L. Anger; Matthew J. Buccilli; Cynthia K. Damer (Cell Adhesion & Migration)
Copines are a family of calcium-dependent membrane-binding proteins. To study these proteins, anull mutant for cpnC was created in Dictyostelium, which has six copines genes (cpnA-cpnF). During development, cpnC− cells were able to aggregate, but did not form streams. Once aggregated into mounds, they formed large ring structures. cpnC− cells were less adherent to plastic substrates, but more adherent to other cells. These phenotypes correlated with changes in adhesion protein expression with decreased expression of SibA and increased expression of CsaA in developing cpnC− cells. We also measured the expression of RegA, a cAMP phosphodiesterase, and found that cpnC− cells have reduced RegA expression. The reduced RegA expression in cpnC− cells is most likely responsible for the observed phenotypes.